PARP1-produced poly-ADP-ribose causes the PARP12 translocation to stress granules and impairment of Golgi complex functions. Issue 1 (December 2017) - Catara, Giuliana; Grimaldi, Giovanna; Schembri, Laura; Spano, Daniela; Turacchio, Gabriele; Lo Monte, Matteo; Beccari, Andrea; Valente, Carmen; Corda, Daniela
Abstract Poly-ADP-ribose-polymerases (PARPs) 1 and 2 are nuclear enzymes that catalyze the poly-ADP-ribosylation of nuclear proteins transferring poly-ADP-ribose (PAR) polymers to specific residues. PARPs and PAR intervene in diverse functions, including DNA repair in the nucleus and stress granule assembly in the cytoplasm. Stress granules contribute to the regulation of translation by clustering and stabilizing mRNAs as well as several cytosolic PARPs and signaling proteins to modulate cell metabolism and survival. Our study is focused on one of these PARPs, PARP12, a Golgi-localized mono-ADP-ribosyltransferase that under stress challenge reversibly translocates from the Golgi complex to stress granules. PARP1 activation and release of nuclear PAR drive this translocation by direct PAR binding to the PARP12-WWE domain. Thus, PAR formation functionally links the activity of the nuclear and cytosolic PARPs during stress response, determining the release of PARP12 from the Golgi complex and the disassembly of the Golgi membranes, followed by a block in anterograde-membrane traffic. Notably, these functions can be rescued by reverting the stress condition (by drug wash-out). Altogether these data point at a novel, reversible nuclear signaling that senses stress to then act on cytosolic PARP12, which in turn converts the stress response into a reversible block in intracellular-membrane traffic.